The Influence Of Work Stress On Employee Performance At Gramedia Basuki Rahmat Malang - Dewi Latifa; Catharina Aprilia Hellyani; Hartomy Akbar Basory; Uki Yonda Asepta; I Gusti Ngurah Agung Arya Bhakta Narayana (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Gramedia Malang Basuki Rahmat faces challenges in maintaining employee productivity due to work-related stress arising during the store renovation process. This study seeks to assess the degree to which such stress influences employee effectiveness. A quantitative framework guides the study, involving a total employee of 70 individuals. From this group, 41 employees were deliberately selected based on predetermined qualifications using a purposive sampling method. Primary data was gathered through employee responses to structured questionnaires, while supplementary insights were drawn from diverse scholarly references. Data acquisition relied on a questionnaire utilizing a Likert scale, followed by rigorous reliability and validity assessments. The analytical process incorporated descriptive evaluation, statistical prerequisite examination, simple linear regression analysis, hypothesis verification, and coefficient of determination assessment. The results reveal that work stress exerts a substantial adverse effect on employee performance. These results provide a foundation for human resource management in formulating strategies to mitigate work stress, ensuring that employee performance remains optimal.